Investigation of TORCH seroprevalence in a tertiary university hospital - Samet Kirat (Medicine Science)
This study aimed to investigate the seroprevalence of TORCH (Toxoplasma gondii, other agents, Rubella, Cytomegalovirus (CMV), and herpes simplex virus (HSV)) in pregnant women at a tertiary university hospital and determine the level of immunity in the community. This retrospective study included 1,556 pregnant women aged 18-50 years who visited the Department of Obstetrics and Gynecology between January 2022 and January 2024. Demographic data and TORCH antibody test results were collected from medical records. Seroprevalence rates were compared between the 18-35 and 35-50 age groups. Avidity test results were recorded for pregnant women with positive IgM antibodies against Toxoplasma, Rubella, and CMV. Seroprevalence rates were Toxoplasma IgM (0.3%), Toxoplasma IgG (76%), Rubella IgM (0.4%), Rubella IgG (96.7%), CMV IgM (0.2%), CMV IgG (97.2%), HSV IgG (97.8%), HBsAg (0.6%), Anti-HBs (18.1%), Anti-HCV (0.3%), and Anti-HIV (0.1%). The frequency of previous infections and proportion of vaccinated individuals increased in pregnant women aged 35-50 years. Avidity tests were performed on pregnant women with positive IgM antibodies against Toxoplasma, Rubella, and CMV to confirm the primary infection. The seroprevalence of TORCH infections in pregnant women at a tertiary university hospital was determined, with a higher proportion of previous infections and immunized individuals in the older age group. The results highlight the importance of prenatal screening for TORCH infections to prevent potential complications and guide health policies for infection control strategies. [Med-Science 2024; 13(4.000): 995-1000]